INVESTIGATION OF THE IMPACT OF HAIL STRIKES ON THE STRENGTH OF CARBON COMPOSITES IN AIRCRAFT STRUCTURES - Semak, Inna; Borozenets, Hryhorii (Problems of Friction and Wear, 2025)
This paper presents the results of an experimental study on the impact of hail strikes on the residual strength of carbon-fiber composite materials used in aircraft structures, particularly fuselage skins. A special method was developed to form ice pellets and apply damage simulating hail impact when an aircraft is stationary. Samples with various reinforcement schemes were tested under two different molding pressure regimes. The findings show that, in most cases, hail impact does not cause significant reduction in material strength. In some cases, a slight increase in strength was observed, likely due to experimental variability. The study provides valuable insights into the potential damage risks from hail to aircraft structures and highlights the relevance of further research in this field to enhance the reliability and durability of aerospace components.